THE DATA-DRIVEN MARKETER: MANAGING CAMPAIGNS WITH ANALYTICS AND AI INSIGHTS - Sri Andika; Lukmanul Hakim; Dahrul Aman Harahap (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The proliferation of data and artificial intelligence promises unprecedented precision in marketing, yet many organizations struggle to translate these resources into improved campaign performance and decision-making. This study investigates the practices and competencies that define the effective data-driven marketer in the age of AI. The objective is to develop a framework for integrating analytics and AI insights into the core processes of campaign strategy, execution, and optimization. Employing a mixed-methods approach, the research combined a survey of 250 marketing professionals with in-depth interviews with 30 analytics leaders and marketing practitioners. The results identify a three-tiered maturity model, highlighting the critical transition from descriptive reporting to predictive and prescriptive analytics, enabled by AI. The discussion focuses on the necessary skill evolution, organizational structures that bridge data and marketing teams, and the ethical governance of AI-driven decisions. It is concluded that becoming truly data-driven requires a fundamental shift in mindset, where analytics and AI are not support functions but the central nervous system of marketing, enabling agile, evidence-based management of the entire campaign lifecycle.